2010
DOI: 10.1038/onc.2010.487
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-221/222 confers breast cancer fulvestrant resistance by regulating multiple signaling pathways

Abstract: Fulvestrant is a selective estrogen receptor downregulator (SERD) and highly effective antagonist to hormone-sensitive breast cancers following failure of previous tamoxifen or aromatase inhibitor therapies. However, after prolonged fulvestrant therapy, acquired resistance eventually occurs in the majority of breast cancer patients, due to poorly understood mechanisms. To examine a possible role(s) of aberrantly expressed microRNAs (miRNAs) in acquired fulvestrant resistance, we compared antiestrogen-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
240
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(252 citation statements)
references
References 68 publications
4
240
3
Order By: Relevance
“…In breast cancer, the role of miRNAs in tamoxifen resistance, through regulation of cell cycle regulatory proteins, has been suggested. In particular, ectopic expression of miR-101, miR-206 and miR-221/miR-222 was found to render ER-positive MCF-7 cells resistant to tamoxifen (150)(151)(152)(153). These miRNAs were also found to be significantly increased in Her2-positive primary human breast cancer tissues indicating an interrelationship between miR-221/222 expression and Her2 overexpression in primary breast tumors that are generally resistant to tamoxifen therapy.…”
Section: Role For Autophagy In Anti-estrogen Resistancementioning
confidence: 95%
“…In breast cancer, the role of miRNAs in tamoxifen resistance, through regulation of cell cycle regulatory proteins, has been suggested. In particular, ectopic expression of miR-101, miR-206 and miR-221/miR-222 was found to render ER-positive MCF-7 cells resistant to tamoxifen (150)(151)(152)(153). These miRNAs were also found to be significantly increased in Her2-positive primary human breast cancer tissues indicating an interrelationship between miR-221/222 expression and Her2 overexpression in primary breast tumors that are generally resistant to tamoxifen therapy.…”
Section: Role For Autophagy In Anti-estrogen Resistancementioning
confidence: 95%
“…Recently, it has been indicated that these miRNAs induce resistance to the selective ER downregulator, and this was caused by the activation of β-catenin and the repression of transforming growth factor-β-mediated growth inhibition. 54 Lu et al 55 demonstrated that miR-221, miR-222 and miR-181b directly target tissue inhibitor of metalloproteinases (TIMP)3, and MCF7 cells that had been subjected to TIMP3 knockdown were found to be able to Figure 2 Biogenesis and function of microRNA (miRNA). miRNA genes are transcribed by RNA polymerase II (Pol II) in the nucleus to generate primary miRNA (pri-miRNA).…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…miRNAs are also associated with chemosensitivity and radiation sensitivity. miR-221/222 are overexpressed in fulvestrant-resistant breast cancer cells and are associated with the acquisition of fulvestrant resistance [113] . Furthermore, up-regulation of miR-221/222 in breast cancer cells also causes tamoxifen resistance by targeting p27 [114] .…”
Section: Implications Of Cell Cycle-related Mirnas In Anti-cancer Thementioning
confidence: 99%